Effects of Anchovy, Mussel, and Shrimp Powders on the Flame Retardancy of Bacterial Cellulose - Hyunjin Kim; Juneyoung Minn; Hye Rim Kim (Journal of Natural Fibers)
This study aims to fabricate bacterial cellulose with improved flame retardancy by applying anchovy, mussel, and shrimp powders. The elemental analysis confirmed that raw marine powders contained nitrogen and sulfur elements which could play important roles in enhancing the flame retardancy of bacterial cellulose. Thermogravimetric analysis revealed the improved thermal stability of bacterial cellulose following entrapping and crosslinking of the marine powders. The fabricated bacterial celluloses with marine powders had similar levels of flame retardancy as that of bacterial cellulose treated with a commercial flame-retardant, sodium metasilicate nonahydrate, which was confirmed by the vertical flammability test and limiting oxygen index. The char morphology analysis revealed intumescent char on the surface of the samples, confirming the effect of marine powders on the flame retardancy of bacterial cellulose. Moreover, the marine powders were entrapped and crosslinked with bacterial cellulose nanostructures, and the chemical and crystalline structures of bacterial cellulose were retained. This study proposes an efficient method to improve the flame retardancy of bacterial cellulose by introducing marine powders via the combined entrapment and crosslinking method.